Challenges in accounting for heritage assets and the way forward: towards implementing accrual accounting in Malaysia - Norida Basnan,; Mohd Fairuz Md. Salleh,; Azlina Ahmad,; Azizah Mohd Harun,; Ismail Upawi, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2015)
Improved reporting is a vital instrument to better discharge a government's accountability obligations, a trait crucial to a government’s integrity. The Federal Government of Malaysia’s announcement to shift from modified cash to accrual-based accounting can be seen as an effort to improve governmental reporting. This study examines the challenges facing the government in accounting for heritage assets with its shift to accrual accounting. Primary data were collected via interviews with representatives of one ministry and two relevant government departments. The study found that the major challenges in accounting for heritage assets were related to recognition and measurement as well as in the aspects of asset registry and staff competency. The findings and recommendations may assist the government in identifying specific measures to ensure the successful implementation of accrual-based accounting.